Asas sains politik - Kalimuthu, K. Ramanathan (Petaling Jaya, Selangor Darul Elsan, [Malysia] : Fajar Bakti, 1987)
Principles of political science with special reference to Malaysia.
In Malay.
Includes bibliographical references (p. [373]-377) and index.
Keywords: Political science -- Malaysia; Political science